Nomeação de presidente de empresas estatais pelo Governo Federal e reação do mercado medida pelo retorno das ações ordinárias: estudo de evento da Petrobrás e do Banco do Brasil - Kawamoto, Victor Tamura (2018)
According to the existing literature, the disclosure of relevant facts to the market represents an important instrument in the evaluation of investors for the formation of the price of securities traded on the stock exchange. However, state-owned enterprises have a peculiarity because they are controlled by the government and, consequently, used for political purposes. The objective of the research is to analyze whether, at the time of the announcement of the appointment of presidents of state-owned companies that perform a relevant function in the activity level of the companies (Petrobrás and Banco do Brasil), there is a statistically significant reaction in the return of the common shares. To measure the result, he used the statistical methodology of event study. After analyzing the appointments individually, it was found inconclusive to say that there is a statistically significant reaction of the financial market to the announcement of the appointments studied in the first term of the governments of the Presidents of the Republic (Fernando Henrique Cardoso, Luis Inácio Lula da Silva and Dilma Rousseff, succeeded by Michel Temer)